Jack the Tripper - Barretta, Gene (Harcourt, 2008)
Someone is tripping students at Benjamin Dizzy Elementary School and taking their candy and homework, but the resulting nervousness does not quell people's excitement over the upcoming Dizzy Day Parade, when the rule is "anything goes."